Emerging therapeutic targets for retinoblastoma. (2nd November 2022) - Manukonda, Radhika; Narayana, Revu VL; Kaliki, Swathi; Mishra, Dilip K; Vemuganti, Geeta K
ABSTRACT: Introduction: Retinoblastoma (Rb) is an early childhood intraocular tumor of the retina and is managed by multimodal therapeutic approaches. Recent advanced targeted delivery of chemotherapeutic drugs to the eye has improved the possibility of globe salvage. However, enucleation is inevitable for advanced and recurrent Rb. The cumulative knowledge of identification of newer molecular biology tools, exosomal cargo, role of cancer stem cells (CSCs), and its microenvironment in the progression of the diseases warrants a relook at the traditional treatment protocol and explore the feasibility of targeted therapies. Areas covered: This review covers Rb pathobiology, novel molecular-targeted therapeutics, and strategies targeting Rb CSCs and provides an update on potential therapeutic targets such as second messengers and exosomal cargo. Expert opinion: The emergence of early diagnosis and multimodality treatment protocols have significantly improved the clinical outcome of children with advanced Rb; however, the problem of tumor recurrence has not yet been overcome. Improved understanding of the molecular pathways, identification, and characterization of CSCs opens up new targeted therapy approaches. The contemporary evidence from other fields shows promising evidence that combining conservative treatment modalities with targeting therapies specific for CSCs in clinical practice is essential for achieving high globe salvage rate in Rb patients.